Visualization of the cellular uptake of nanoparticles - Adsley, Rosemary (2013)
The effect of nanoparticle charge and conjugation to the cell penetrating peptide Tat on the uptake of nanoparticles into MRC-5 fibroblasts was investigated using a range of advanced imaging techniques including atomic force microscopy (AFM), scanning ion conductance microscopy (SICM) and fluorescence microscopy. New technologies are required to investigate the uptake of nanoparticles since although many studies have examined their destination within cells, little work has been done looking at the interaction between the nanoparticles and cell which also plays an important role.